Patient’s Experiences of Violence as Perpetrator: A Qualitative Study from Patients with Schizophrenia in Indonesia - Iyus, Yosep; Helmy, Hazmi; Zabidah, Putit (2022)
BACKGROUND: Individuals with schizophrenia are at an increased risk for violence – limited study on exploring the experience of violence in patients with schizophrenia as a perpetrator. AIM: This research aimed to investigate the perception of violence as a perpetrator in Indonesia in patients with schizophrenia. METHODS: This study used phenomenology using a purposive sampling technique. A total of 40 patients were from the psychiatric ward of significant mental hospitals in West Java, Indonesia. The inclusion criteria for patients were the following: Age over 18 years old confirmed diagnosis with schizophrenia. Focus group discussion of patients comprised four groups. Each group consisted of tens of patients. RESULTS: The patient’s experiences as a perpetrator were categorized into six subthemes: Committing physical violence to family, quarreling with family, verbal abuse to family, a perpetrator of verbal violence to neighbors, expression of anger to object, and physical violence to nurse. CONCLUSION: The patient’s experiences of violence were not linear, but rather it was a complex experience of being a perpetrator, yet at the same time as of perpetrator violence. A staff training program to reduce patient violence is needed.